2021
DOI: 10.1007/s10815-021-02194-1
|View full text |Cite
|
Sign up to set email alerts
|

Two novel mutations in PADI6 and TLE6 genes cause female infertility due to arrest in embryonic development

Abstract: Purpose This study aims to identify genetic causes of female infertility associated with recurrent failure of assisted reproductive technology (ART) characterized by embryonic developmental arrest. Methods We recruited infertile patients from two consanguineous families from the Reproductive Medicine Center of Guizhou Provincial People’s Hospital. Peripheral blood was collected for genomic DNA extraction. Two affected individuals and their family members w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 29 publications
1
16
0
Order By: Relevance
“…In this study, a homozygous mutation c.558dupA (p.T187Nfs*48) caused early embryonic arrest in the proband (II-2), resulting in 3- or 5-cell arrested embryos on Day 3 and no viable blastocytes on Day 5, which was congruent with previous reports [ 8 , 9 , 23 25 ]. Due to the limitation of the PADI6 antibody for immunofluorescence, we did not investigate the in vivo expression of PADI6 in the oocytes of the patient.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In this study, a homozygous mutation c.558dupA (p.T187Nfs*48) caused early embryonic arrest in the proband (II-2), resulting in 3- or 5-cell arrested embryos on Day 3 and no viable blastocytes on Day 5, which was congruent with previous reports [ 8 , 9 , 23 25 ]. Due to the limitation of the PADI6 antibody for immunofluorescence, we did not investigate the in vivo expression of PADI6 in the oocytes of the patient.…”
Section: Discussionsupporting
confidence: 92%
“…The PADI family is comprised of five members, including PADI1 , PADI2 , PADI3 , PADI4 , and PADI6 . Among these, PADI6 is exclusively expressed in oocytes and early embryos [ 9 ]. PADI6 is one of SCMC components that localizes to other components in oocytes and early embryos.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pathogenic loss-of-function variants in PADI6 have been also described in the mothers of children with sporadic Beckwith–Wiedemann syndrome with MLID [ 61 ]. Biallelic variants in PADI6 cause female infertility characterized as early embryonic developmental arrest, zygotic cleavage failure, and recurrent hydatidiform moles [ 62 , 63 , 64 , 65 , 66 ]. An in vitro expression study showed a significant decrease in PADI6 in mutation models, which may disturb the stability of the SCMC complex [ 62 ].…”
Section: Genes Of Scmc Componentsmentioning
confidence: 99%
“…In mouse models, the knockout of the Tle6 gene has no effect on oogenesis but results in embryonic developmental arrest at the 2-cell stage, leading to female mouse infertility [ 48 , 67 ]. Homozygous and compound-heterozygous variants in the TLE6 gene are associated with various phenotypes, including fertilization failure, early cleavage failure, embryonic developmental arrest on day 3, and a high rate of embryo fragmentation due to the disruption of F-actin and spindle assembly [ 14 , 66 , 68 , 69 ]. A woman with a heterozygous variant in TLE6 had normal fertility and two healthy children [ 69 ].…”
Section: Genes Of Scmc Componentsmentioning
confidence: 99%